Ekonomi dan Peran Perempuan di Hindia Belanda pada Abad XIX-XX - Khairunnisa Pasaribu, Riska (Siginjai: Jurnal Sejarah, 2024)
This article will discuss the economic conditions and roles of women under the colonial rule of the Dutch Hindia..Economic insistence and a lack of jobs for women are a major factor in the emergence of anxiety, A prostitute's work is non-reformal and yet there are also entrepreneurs in Hindia dutch..Redevelopment developments were increasing at the end of the 19th century to the early 20th century., That's when the colonial government hindia dutch practiced liberal economics in hindia dutch..The liberal economic system is marked by freedom of business as a private investment in plantations and mining..As for the method used in this writing is the method of history.The results of this study show that in the days of the dutch colonial, Women have a double role in doing domestic work or domestic work and also have a role as earners to care for economic needs and welfare. The practice of prostitution and prostitution became common in the Dutch India as one of the searching eyes done by the women of the bumiputra then, But not less important is the emergence of female entrepreneurs who show the great role of women in the economy in the Dutch Indies in the XIX- XX century. Keywords: Dutch east Indish, economic, women role